Criminal law - Pollock, Joycelyn M., 1956- (Routledge, Taylor & Francis Group, 2021)
"Criminal Law, Twelfth Edition, a classic introduction to criminal law for criminal justice students, combines the best features of a casebook and a textbook. Its success over numerous editions, both at community colleges as well as in four-year college criminal justice programs, is proof this text works as an authoritative source on criminal law as well as a teaching text that communicates with students. The book covers substantive criminal law and explores its principles, sources, distinctions, and limitations. Definitions and elements of crimes are explained, and defenses to crimes are thoroughly analyzed. Each chapter offers guidance to help students understand what is important, including chapter outlines, key terms, learning objectives, Legal News boxes that highlight current criminal law issues, and Quick Checks that cue the reader to stop and answer a question or two concerning the material just covered. Unique Exploring Case Law boxes offer guidance in using the accompanying cases, which are provided on the book's website. A robust collection of instructor support materials addresses teaching and learning issues. Updated with all the newest relevant law, this book is appropriate for undergraduate students in criminal law and related courses. A robust companion site offers instructor's aides with test bank and PowerPoint lecture slides as well as a companion site with student resources"--